Multi-product pricing: Theory and evidence from large retailers in Israel - Marco Antonio Bonomo; Carlos Viana de Carvalho; Oleksiy Kryvtsov; Sigal Ribon; Rodolfo Rigato (Bank of Canada, 2020)
Standard theories of price adjustment are based on the problem of a single-product firm, and therefore they may not be well suited to analyze price dynamics in the economy with multiproduct firms. To guide new theory, we study a unique dataset with comprehensive coverage of daily prices in large multi-product food retailers in Israel. We find that a typical retail store synchronizes its regular price changes around occasional "peak" days when, once or twice a month, it reprices around 10% of its products. To assess the implications of partial price synchronization for inflation dynamics, we develop a new price-setting model in which a firm sells a continuum of products and faces economies of scope in price adjustment. The model generates the partial synchronization pattern with peaks of re-pricing activity observed in the data. We show analytically and numerically that synchronization of price changes attenuates the average price response to a monetary shock; however, only high degrees of synchronization can materially strengthen monetary non-neutrality. Hence, the synchronization of price changes observed in the data is consistent with considerable aggregate price flexibility.
Keywords: D21; D22; E31; E52; L11; 330; Inflation and prices; Market structure and pricing; Monetary policy